KONSEP PEMERINTAHAN DALAM ISLAM MENURUT ABU AL-A’LA AL-MAUDUDI SERTA KEMUNGKINAN PENERAPANNYA DI INDONESIA - Otoluwa, Andhika Pratama Putra; Umar, Kusnadi (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2024)
Differences in views regarding governance in Islam have caused debate among the people, for that al-Maududi tries to answer this problem by returning to the Qur'an, the sunnah, and the example given by Khulafa al-Rasyidun. This study aims to determine the system of government in Islam and the division of power according to Abu al-A'la al-Maududi and the possibility of its application in Indonesia. The research method used is library research, with a normative syar'i and philosophical approach. The results show that the Islamic government system according to Abu al-A'la al-Maududi can be grouped as a caliphate Islamic government system based on shura. Power is divided into legislative (ahl al-hal wa al-aqd), executive (ulu al-amr) and judicial (qadha). The application of the concept of Islamic government according to Abu al-A'la al-Maududi in Indonesia is faced with opportunities in the form of the existence of Islamic law in Indonesia, the view of Indonesia as an Islamic state and Islamic values ​​in line with the nation's goals. The obstacles faced are the plurality of Indonesia, the view that there is no need to establish an Islamic state and the rejection of women's groups. The challenge is in the form of nationalist Islamic intellectual groups and secularization.